Probing the stability of thin-shell space structures under bending. (5th December 2022) - Royer, Fabien; Hutchinson, John W.; Pellegrino, Sergio
Abstract: The stability of lightweight space structures composed of longitudinal thin-shell elements connected transversely by thin rods is investigated, extending recent work on the stability of cylindrical and spherical shells. The role of localization in the buckling of these structures is investigated and early transitions into the post-buckling regime are unveiled using a probe that locally displaces the structure. Multiple probe locations are studied and the probe force versus probe displacement curves are analyzed and plotted to assess the structure's stability. The probing method enables the computation of the energy input needed to transition early into a post-buckling state, which is central to determining the critical buckling mechanism for the structure. A stability landscape is finally plotted for the critical buckling mechanism. It gives insight into the post-buckling stability of the structure and the existence of localized post-buckling states in the close vicinity of the fundamental equilibrium path.